Impact of Celebrity Endorsers from a Country of Animosity on Consumer Attitude when Used in Sponsored Anti Polio Campaigns: A Case of Pakistan. - Afzal, Zainab (2016)
Purpose – The purpose of the present study is to understand the impact that celebrity endorser from a country of animosity has on consumer attitude when used in cause related marketing and how cosmopolitism plays an important role in determining the magnitude of impact the animosity has on attitude of the consumer. Methodology – Online surveys were employed to collect data from 250 Pakistani consumers through convenience sampling. To further analyze the data SPSS statistics 20 was used. Findings – The results show that attitude towards the ad, attitude towards the brand and word of mouth will be more positive for ads with Afridi (Pakistani celebrity) than for ads with Dohni (Indian Celebrity). It also shows that level of cosmopolitism has no impact on the attitude towards the ad and the sponsoring brand (Pepsi). Practical implications – The concept of animosity and ‘international celebrities’ is vital in today’s globalized world. This study can be used to develop theories on how animosity impacts the effectiveness of celebrity endorsement. Animosity, celebrity endorsement and cause related marketing is of growing concern to the marketers. This study will assist the marketers in understanding these three concepts and then carefully evaluating and developing their marketing strategies. Originality/Value – Regardless of the previous and extensive research on celebrity endorsements and animosity, this study sheds light on the concepts from a different perspective. It brings together different prevailing concepts in today’s marketing world.